Sistem Informasi Rekap Data Pengambilan Ijazah Berbasis Web di SMK Wihdatul Ummah Gondangrejo - Kiki Putri Priyanti; Eka Budhi Santosa; Mursid Dwi Hastomo (Indonesian Journal of Information Technology and Computing (IMAGING), 2024)
The information system for recapturing diploma collection data at SMK Wihdatul Ummah is still done manually by writing in a general book to find out the data of all students who have or have not taken their diplomas. So that a web-based information system is needed that helps the process of recapitulation of diploma data, the information system designed will use the PHP (Hypertext Preprocessor) programming language and the mySQL database while the structured method in the development of information systems or applications to be made is the System Development Life Cycle (SDLC) the author makes a web-based information system because the managed data can be accessed easily and more efficiently data  will be safer because it is not easily accessed by just anyone, from the creation of an information system or a web-based data recap application is expected to facilitate the data recapitulation process and reduce the risk of losing data that is recorded manually, the use of a diploma recap data information system will make it easier to store data or change certain data.